Microstructure Evolution during Cold-Deformation and Aging Response after Annealing of TB8 Titanium Alloy. Issue 3 (March 2016) - Xu, Tiewei; Li, Jinshan; Zhang, Fengshou; Wang, Feiyun; Liu, Xianghong; Feng, Yong
Abstract: The microstructure evolution of titanium alloy is decided by deformation degree in cold-deformation process, and substructures resulting from different cold deformations significantly influence phase transformation behavior in isothermal aging treatment. The microstructure evolution in cold-deformation and the followed aging behavior of TB8 alloy were investigated by X-ray diffraction (XRD), Vickers hardness (HV), field emission scanning electron microscope (FESEM) and differential scanning calorimeter (DSC). Results show that the high value of FWHM results from the combination of the grain distortion and dislocations, and the enhancement of the distortion and dislocations is accompanied by increasing of HV value. The phase transformation of the present investigation exhibits the effect of cold-deformation on transformation behavior of α phase precipitation in the β matrix. It is suggested that there is a distinctive behavior in the aging transformation of cold-deformed titanium alloy.